THE RECONSTRUCTION OF GIBELLINA AFTER THE BELICE EARTHQUAKE OF 1968 - Scibilia, Federica (International Planning History Society Proceedings, 2016)
On 15 January 1968 a catastrophic earthquake struck fourteen towns of the Belice Valley. In half of the cases in the reconstruction plans it was decided to abandon and raze the old settlements affected by the earthquake and to build new ones in different places and not always close to their original centers. These ‘new’ cities were specifically Gibellina, Santa Margherita Belice, Vita, Menfi, Santa Ninfa, Montevago and Poggioreale. Among these centers Gibellina was the most damaged and the town was built about 18 kilometers away from the old settlement in an area within Salemi, where the highway and the railroad converged, in an attempt to take away the new center from the isolation in which it had lived for centuries. For the reconstruction of the town, similarly to what happened to other centers of Belice, a development plan was drawn up by the Istituto per l'Edilizia Sociale (ISES). The ISES, established by Italian Act No. 133 of 15 February 1963, was presented as a technical Rome-headquartered body in charge of social housing across the country and was also responsible for intervening in cases of housing reconstruction after public disasters. This Institute was assigned the task to elaborate the general plan, designed in an extensive urban model alien to the identity of the local population, was also responsible for the primary and secondary urbanization works, including the construction of social housing, school buildings (kindergarten and secondary school), a cemetery and a community center, in addition to the construction of a cattle and vegetable markets. At the same time the earthquake was the pretext for experimenting with significant projects by famous architects and artists, who were called to intervene in the new center by the then Mayor Ludovico Corrao. These professionals contributed to reconstruct the city and to make Gibellina a real ‘museum’ of modern architecture. Significant examples of the great cultural ferment that swept Gibellina since the seventies are the Cathedral by Ludovico Quaroni, the Secret Gardens by Francesco Venice, the Porta del Belice by Pietro Consagra, the system of squares designed by Laura Thermes and Franco Purini with the Civic Tower by Alessandro Mendini. This study aims going deeply into the case of Gibellina by analysing its new urban plan and its architectures, that represents a unicum among the cities rebuilt after strong earthquakes. For this research a variety of bibliographical and archival sources, especially the ISES fund, kept in the State Archive of Palermo, will be consulted. Particular attention will be given to the comparison between the case-study of Gibellina and the other towns of Belice destroyed by the earthquake in which the construction of the ‘new’ cities designed to replace the old centers has created identity problems that are still unsolved.